2000
DOI: 10.2214/ajr.175.2.1750407
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Value of Thin Collimation in the Diagnostic Workup of Pulmonary Embolism

Abstract: Thin-collimation helical CT provided technically acceptable examinations for pulmonary embolism in 360 patients (97%). In this population, CT revealed pulmonary embolism in 104 patients (29%), negative findings in 217 patients (59%), indeterminate findings in 39 patients (10%), and alternative diagnoses in 65% of patients with negative or inconclusive findings. Ventilation-perfusion scanning and Doppler sonography of the lower extremities were performed in 158 (44%) and 133 patients (37%), respectively, wherea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0
5

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(61 citation statements)
references
References 12 publications
1
55
0
5
Order By: Relevance
“…Such partial identification of vessels may create false-positive and false-negative results or lead the observer to an indeterminate answer [13]. Using thin-collimation and subsecond single-slice CT, Remy-Jardin et al have previously reported significant improvement in image quality due to a higher spatial resolution, resulting from a higher rate of analyzable segmental pulmonary arteries and a reduction in interpretive difficulties due to volume averaging [5,6]. Further improvement has recently been shown with multislice CT enabling an accurate analysis of peripheral pulmonary arteries down to the fifth order [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such partial identification of vessels may create false-positive and false-negative results or lead the observer to an indeterminate answer [13]. Using thin-collimation and subsecond single-slice CT, Remy-Jardin et al have previously reported significant improvement in image quality due to a higher spatial resolution, resulting from a higher rate of analyzable segmental pulmonary arteries and a reduction in interpretive difficulties due to volume averaging [5,6]. Further improvement has recently been shown with multislice CT enabling an accurate analysis of peripheral pulmonary arteries down to the fifth order [8].…”
Section: Discussionmentioning
confidence: 99%
“…An important step was the availability of subsecond scanning in the late 1990s which allowed scanning of patients with thinner collimations, i.e., 3-to 2 mm, over a longer region of interest. Whereas this optimization of technical factors allowed marked improvement in the evaluation of the segmental pulmonary arterial bed, there remained limitations in the evaluation of subsegmental pulmonary arteries [5,6]. With a recent increase in gantry speed from one to two revolutions per second, multisection CT scanners are now up to eight times faster than conventional single-section spiral CT scanners, allowing greater anatomic coverage and better longitudinal resolution during a single breath hold [7].…”
Section: Introductionmentioning
confidence: 99%
“…The diagnosis of pulmonary embolism on CTPA is based on finding filling defects within the contrast-enhanced lumens of the pulmonary arteries or direct observation of an intra-luminal clot. 15,16 Typical manifestations of embolus on CT include the "lifesaver" sign perpendicular to the long axis of the vessel, the "railway track" sign on longitudinal images of the vessel, and the Westermark sign, which refers to peripheral wedge-shaped regions of ground-glass opacity or consolidation. [17][18][19] However, in our patient the sharp artery cutoff on CTPA (arrow in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Although normal V/Q scintigraphy essentially excludes PE, a high-probability V/Q scan has a sensitivity of 88% for PE compared with pulmonary angiography. In the prospective investigation of pulmonary embolism diagnosis (PIO-PED) study, only 41% of patients with PE had a highprobability scan, 7 and 57% of patients had nondiagnostic (indeterminate or low-probability) V/Q scans.…”
Section: Ct Pulmonary Angiographymentioning
confidence: 99%